Avaliação do relacionamento entre sustentabilidade e desempenho exportador nas exportações de carne bovina - Flores, Francisco Sperotto (Universidade do Vale do Rio dos Sinos, 2015)
The purpose of this study is evaluating the relationship between sustainability and the export performance of beef exporters. It is used panel data analysis form the collection of secondary data of exports of fresh or chilled beef with regard to Italy, Dutch, French, Mexican, Japanese, German and the UK between the years 2002 and 2012, totaling an average of 125 observations for each importing country. The sustainability of exporters was evaluated through its social performance, using as proxy the Human Development Index (HDI), and environmental performance, evaluated from the Net Adjusted Savings (ANS). The results obtained by econometric analysis show that the social dimension of sustainability has a positive influence on the export performance of refrigerators exporters of beef, while the environmental dimension of sustainability is associated with the input capacity and maintenance of these companies in the international beef market. Although the analysis uses data at the country level, given the hight concentration level in the meat export industry and also that value chain and the beef international market are dominated by a small group of large companies with global presence, it is considered that, by analyzing the behavior of trade between countries, it is possible to infer the commodity trading behavior at firm level.
Keywords: Desempenho exportador; Sustentabilidade; Desempenho social; Desempenho ambiental; Export performance; Sustainability; Social performance; Environmental performance; ACCNPQ::Ciências Sociais Aplicadas::Administração